Googling Service Boundaries for Endovascular Clot Retrieval (ECR) Hub Hospitals in Metropolitan Sydney - Phan, Thanh G.; Beare, Richard; Srikanth, Velandai; Ma, Henry (Frontiers in Neurology, 2019)
Background and Purpose: Endovascular clot retrieval (ECR) has revolutionized acute stroke therapy. This service is expensive to run and staff 24/7; consequently, it is only feasible for each metropolitan city to have a minimum number of hubs that is adequate to service the population. This method is applied to search the minimum number of hospitals to be designated as ECR hubs in Sydney as well as the population at risk of stroke reachable within 30 minutes. Methods: Traveling time from the centroids of each suburbs to five ECR capable hubs [Royal Prince Alfred/RPA, Prince of Wales/POW, Royal North Shore/RNS, Liverpool/LH and Westmead/WH]. This step was performed using ggmap package in R to interface with Google Map application program interface (API). Next, we calculate the percentage of suburbs within each catchment in which traveling time to the ECR hub is less than 30 minutes. This step was performed for all possible combination of ECR hubs. The maps are available at https://gntem3.shinyapps.io/ambsydney/. The population at risk of stroke was estimated using stroke incident studies in Melbourne and Adelaide. Results: The best 3-hospital combinations are LPH/WH/RNS (82.3%, 45.7% and 79.7% of suburbs reachable within 30 minutes or 187 of 226 suburbs) follow by RPA/LPH/RNS (100.0%, 80.9% and 73.1% of suburbs) and LPH/POW/RNS (83.3%, 90.7% and 76.6% of suburbs). The best 4-hospital model is LPH/WH/POW/RNS (84.2%, 91.1%, 90.7%, 77.8%). In the 5-hospital model, ECR is available for 191 suburbs within 30 minutes: LPH (83%), RPA (100%), WH (90.2%), RNS (72.7%), POW (88.9%). Based on 3-hospital model and 15% of patient eligible for ECR, the expected number of cases to be handled by each hospital is 465. This number drops down to 374 if a 4-hospital model is preferred. Conclusions: The simulation studies supported a minimum of 4 ECR hubs servicing Sydney. This model provides data on number of suburbs and population at risk of stroke that can reach these hubs within 30 minutes.